Helium and strontium isotopes in ultramafic xenoliths - Porcelli, DR; O'Nions, R; O'Reilly, S (1986)
The isotopic compositions of He and Sr have been obtained for suites of ultramafic xenoliths brought to the surface by Recent volcanic eruptions in continental environments. Samples include a range of petrologic types from Lashaine, Eledoi and Pello Hill (Tanzania), Bullenmerri maar (Victoria, Australia), Puy Beaunit (Massif Central, France) and Ataq (South Yemen). Primordial mantle He was found in all samples, with whole-rock analyses yielding 3He 4He ratios (R) that show a restricted range from 6 to 10 times the atmospheric ratio (RA). This is within the documented range for mid-ocean ridge basalts and indicates that the He at these diverse locations, and by implication associated fluids such as CO2, are derived from the same mantle circulation as sampled by volcanicity at spreading ridges. Small but significant intermineral differences between coexisting olivine and clinopyroxene are due to minor radiogenic additions of He in the latter. Although the xenoliths exhibit a relatively uniform He isotopic signature, separated clinopyroxenes have 87Sr 86Sr ratios that vary from 0.7036 to 0.8360, and demonstrate a complete decoupling of the isotopes of He from those of the lithophile trace elements. © 1986.